Penalaran Matematis Mahasiswa dalam Menyelesaikan Masalah Trigonometri - Sari, Feti Eka Ratna; Sa'dijah, Cholis; Chandra, Tjang Daniel (Universitas PGRI Madiun, 2023)
Important for students to have reasoning abilities in learning mathematics. This is due to the relationship between mathematics and reasoning. The purpose of this study is to analyze students' mathematical reasoning abilities in solving trigonometry problems. This type of research is descriptive qualitative. As many as 36 students in class D semester 1 of mathematics education at State University of Malang were the subjects of this study. Methods of data collection obtained from the implementation of trigonometry problem tests and interviews. Data analysis with three stages namely reduction techniques, presentation, and drawing conclusions. This study resulted in the conclusions (1) students with high abilities met all indicators, namely making conjectures, performing mathematical manipulations, compiling evidence, and drawing conclusions, (2) students with moderate abilities fulfilled two indicators, namely making conjectures and compiling evidence, while (3) students who were low ability to fulfill one indicator, namely submitting conjectures.